OPTIMALISASI KUALITAS JARINGAN INTERNET DENGAN METODE PEER CONECTION CLASSIFIER PADA LAYANAN WEB AUTENTIFICATION - Toni Sukendar (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
Along with the increasing need to used existing resources in the development of computer network technology has led to the emergence of the network itself. Availability of resources will be inversely proportional to the level of need are now demanding networking technologies floated a new technique that can resolve the issue. Load balancing is a technique that can harness routing multiple resources to be used simultaneously. However, there are various methods that can also be used, including methods of NTH, PCC load balancing and Fail Over. This study discusses the PCC Load Balancing Methods In Autentification are accessing the web, which is considered as needed. The implementation of load balancing so that resources are used optimally.